2014
DOI: 10.1007/s12205-014-0558-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcite precipitation by ureolytic plant (Canavalia ensiformis) extracts as effective biomaterials

Abstract: An extract of the indigenous plant jack bean (Canavalia ensiformis) was used to produce calcite, an effective biomaterial. The formation of calcite using this extract was compared, under stable conditions, to that using commercially available purified urease. Xray diffraction and scanning electron microscopy were employed to elucidate the mechanism of calcite formation from the crude plant extracts. The results revealed that urease in the jack bean crude extracts catalyzed the hydrolysis of urea in liquid-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Among these applications are amending or improving construction materials and remediation of cracks/self-healing in concrete [3, 72, 79-86, 102, 118-122], as well as cementation of porous media and improvements in strength and stiffness [6,7,26,35,103,117,121,123]. It is also used in environmental remediation of heavy metals and radionuclides, including the potential to reduce subsurface leakage in the background of geologically isolated carbon dioxide [72,104,105,[124][125][126][127][128][129][130][131][132][133][134][135]. Recent studies [136] have reported MICP as a conservative method for restoring the lost strength in decayed limestone through biomineralization processes, for trial tests in both laboratory and field conditions.…”
Section: Micp Applicationsmentioning
confidence: 99%
“…Among these applications are amending or improving construction materials and remediation of cracks/self-healing in concrete [3, 72, 79-86, 102, 118-122], as well as cementation of porous media and improvements in strength and stiffness [6,7,26,35,103,117,121,123]. It is also used in environmental remediation of heavy metals and radionuclides, including the potential to reduce subsurface leakage in the background of geologically isolated carbon dioxide [72,104,105,[124][125][126][127][128][129][130][131][132][133][134][135]. Recent studies [136] have reported MICP as a conservative method for restoring the lost strength in decayed limestone through biomineralization processes, for trial tests in both laboratory and field conditions.…”
Section: Micp Applicationsmentioning
confidence: 99%
“…๏‚ท Further advancements with characterizing and optimizing the procurement, performance, D r a f t Nemati and Voordouw 2003;Nemati et al 2005Larsen et al 2008Bang et al 2009Yasuhara et al 2011Handley-Sidhu et al 2013Neupane et al 2013, 2015ab Hamdan et al 2013b Hamdan et al , 2016Kavazanjian and Hamdan 2015;Kavazanjian et al 2017Nam et al 2014Park et al 2014Putra et al 2016 Un-treated Note: a average; b standard deviation; c relative error necessary for log-based plots (Baird 1994); d not analyzed…”
Section: Future Research Recommendationsmentioning
confidence: 99%
“…Crude extracts of jack bean (Canavalia ensiformis) also have the potential to be used instead of commercially available purified urease due to similar rates of calcite formation. 9) Furthermore, sword beans urease was also used to reduce the permeability by more than one order of magnitude and to increase unconfined compressive strength value up to 1620 kPa by producing CaCO 3 . 10) There are few laboratory scale studies on sand cementation technique via plant-derived urease related to geotechnical and rock engineering.…”
Section: Plant-derived Ureasementioning
confidence: 99%